The high burden of erectile dysfunction among men living with HIV in northern Tanzania: a call for evidence-based interventions - Mbwambo, Orgeness J.; Lyatuu, Moses; Ngocho, Geofrey; Abdallah, Khadija; Godfrey, Patricia; Ngowi, Bartholomeo N.; Mremi, Alex; Malindisa, Evangelista; Amour, Maryam; Ngocho, James; Balandya, Emmanuel; Kwesigabo, Gideon; et al. (Frontiers in Urology, 2023)
The high burden of Erectile dysfunction(ED) among men living with HIV (MLHIV) and associated risk factors remains unclear. The aim of this study was to investigate the factors associated with ED and its prevalence among MLHIV in Northern Tanzania. A hospital-based multi-centered cross-sectional study conducted among MLHIV aged 18 years and above in Northern Tanzania. The risk factors for ED and the prevalence of such risk factors among MLHIV was assessed and evaluated through a multivariate logistic regression adjusted for depression symptoms using the Patient Health questionnaire-9 scale(PHQ9), anxiety disorders using the Generalized anxiety Disorder Assessment(GAD-7),ART adherence, viral load, initial regimen date, ART regimen and sexual risk behaviour. Data of 366 participants with median age of 50 years (IQR 38-57) was available for analysis. About three in four (74.6%) MLHIV had ED, whereas 37.7% had mild ED. Majority (96.5%) of the participants had low testosterone, two in three (66.7%) had depressive symptoms, and close to half of the participants (48.4%) had anxiety. Age, absence of vigorous activities, depression and self-reported good adherence to antiretroviral therapy (ART) were associated with ED in multivariate logistic regression (p=0.004, p- =0.006, p=0.07 , p=0.006 and p=0.004 respectively ). There is a high prevalence of ED among MLHIV in Northern Tanzania. Erectile Dysfunction should be regarded as one of the co-morbidities associated with HIV and should be routinely screened among MLHIV in CTC clinics.